Research and evidence in education decision-making: A comparison of results from two pan-Canadian studies - Galway, Gerald; Sheppard, Bruce (Education Policy Analysis Archives, 2015)
In this paper we compare the use of research and other evidence in the policy formation practices of two groups of education policy elites, situated in different contexts – provincial education ministries and school districts. Data are derived from two pan-Canadian studies: Galway (2006) and Sheppard, Galway, Brown & Wiens (2013). The findings show that policy decisions at the ministry level are informed primarily by political and pragmatic factors, personal and professional beliefs and staff advice. The role of external research is shown to be relatively marginal and confined to quantitative studies and performance assessments. Decision makers at the school district level are less attendant to political and pragmatic influences relying more on personal beliefs, values and experiential factors supplemented by the advice of professional staff and in-house research/indicators. Results from both studies demonstrate limited reliance on external data and university-based research – the latter ranking 15th of 20 influencing factors. Consistent with Beck’s (1994; 1997) risk theory, we theorize that education policy making in both contexts is influenced by both macro- and micro-level factors, where choice of policy evidence is mediated by personal considerations and political risk factors. This suggests a weak policy development paradigm that is, to a large extent, resistant to independent research-informed evidence.